Representasi sosiopat dalam web series korea it’s okay to not be okay (Faculty of Communications Science, Dr. Soetomo University, 2022)
Web series It's Okay to Not Be Okay illustrates how people with mental health illnesses are still an issue that gets less attention in society. Ko Moon-young's character represents how a sociopath behaves and behaves in his environment with all his shortcomings in self-control. The purpose of this study is to show the representation of a sociopath in the web series It's Okay to Not Be Okay. This study uses a qualitative approach with a descriptive type of research to explain how a sociopath is described through the character of Ko Moon-young. This research uses representation theory with semiotic analysis technique from Charles Sanders Peirce with sign, object, and interpretant. From the results of research which shows that a sociopath thinks that is irrational, selfish, has no empathy, has no shame.